Analisis Kualitas Produk, Nilai Pelanggan, Kepuasan Pelanggan Serta Pengaruhnya terhadap Loyalitas Pelanggan pada PT. Bizza Kurnia Multindo (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to comprehensively examine the influence of product quality, customer value, and customer satisfaction on customer loyalty at PT Bizza Kurnia Multindo. A quantitative research design was employed using purposive sampling, involving 220 active customers as respondents deemed relevant to the research objectives. Data were collected through a structured questionnaire designed to measure respondents’ perceptions of the study variables. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS), which is considered appropriate for testing causal relationships among variables. The findings indicate that product quality and customer value exert a positive and significant effect on customer satisfaction, underscoring the importance of consistent quality and value alignment with customer expectations. Moreover, customer satisfaction functions as a significant mediating variable that strengthens the relationship between product quality, customer value, and loyalty. These results suggest that customer loyalty is shaped not only by product excellence but also by repeated satisfaction experiences and perceived value. From a managerial perspective, the study emphasizes the need to reinforce internal quality management systems, enhance value proposition strategies, and regularly measure customer satisfaction. Future research could extend the model by incorporating additional variables such as service quality, price perception, and product innovation, which may further enrich the understanding of loyalty in increasingly competitive business contexts.